Gene(s) and individual feeding behavior: Exploring eco‐evolutionary dynamics underlying left‐right asymmetry in the scale‐eating cichlid fish Perissodus microlepis. Issue 11 (8th May 2018) - Raffini, Francesca; Fruciano, Carmelo; Meyer, Axel
Abstract: The scale‐eating cichlid fish Perissodus microlepis is a textbook example of bilateral asymmetry due to its left or right‐bending heads and of negative frequency‐dependent selection, which is proposed to maintain this stable polymorphism. The mechanisms that underlie this asymmetry remain elusive. Several studies had initially postulated a simple genetic basis for this trait, but this explanation has been questioned, particularly by reports observing a unimodal distribution of mouth shapes. We hypothesize that this unimodal distribution might be due to a combination of genetic and phenotypically plastic components. Here, we expanded on previous work by investigating a formerly identified candidate SNP associated to mouth laterality, documenting inter‐individual variation in feeding preference using stable isotope analyses, and testing their association with mouth asymmetry. Our results suggest that this polymorphism is influenced by both a polygenic basis and inter‐individual non‐genetic variation, possibly due to feeding experience, individual specialization, and intraspecific competition. We introduce a hypothesis potentially explaining the simultaneous maintenance of left, right, asymmetric and symmetric mouth phenotypes due to the interaction between diverse eco‐evolutionary dynamics including niche construction and balancing selection. Future studies will have to further tease apart the relative contribution of genetic and environmental factors and their interactions in an integrated fashion. Abstract : We analyzed the relationship between genetic and ecological (established individual feeding behavior) variation and morphological asymmetry in the scale‐eating fish Perissodus microlepis. Our results confirm that a candidate SNP and feeding habit are associated with mouth bending angle, providing further support for a complex basis of asymmetry. We introduce a comprehensive hypothesis potentially explaining how these genetic and non‐genetic cues jointly influence the direction and the degree of mouth asymmetry as well as the maintenance of intraspecific variation.